Biology of Mango Pulp Weevil, Sternochetus gravis (Fabr.) (Curculionidae: Coleoptera) in the Agro-ecosystem of Manipur - Devi , A. Binarani Devi and K. Manoj Singh, M. Bhubaneshwari Devi*, A. Kananbala (Journal of Experimental Sciences, 2011)
A study was conducted in the laboratory of Entomology, P.G. Department of Zoology, D.M. College of Science, Imphal during February to July, 2009 at 25± 20C and 75±5% RH (at room temperature and humidity) to study the biology of mango pulp weevil, Sternochetus gravis. The duration of life cycle has been observed to vary from one crop to another crop. Only one crop was observed in a season. The environmental parameters have been observed to play a vital role in the biology of this pest. Adult weevils were nocturnal and began feeding, mating and oviposition at dusk. Male and females mate more than once. The eggs were laid singly by making incisions in the skin of the immature fruits with the help of their ovipositors. These incisions looked like a crescent shaped cut protected by an opaque coating formed by exudation. The eggs hatched in about 7 - 9 days. The five larval instars were observed with four moulting. The larval duration varied from 5 - 8 days in first instar, 6 - 9 days in second instar, 7 - 8 days in the third and fourth instars and 6 to 7 days in the fifth instar respectively. The pupation lasted for about 7 days. The life cycle was completed in 49 - 57 days. The adult emerges during May- July.